(untitled) (Bangladesh Veterinarian, 2012)
Arsenic from groundwater affects people in Bangladesh via seed grains and forages. Samples of rice (Oryza sativa L) and rice straw were collected from arsenic-contaminated areas and arsenic concentration was measured using Flow Injection Hidride Generator Atomic Absorption Spectrophotometer (FI-HG-AAS) method. The concentrations in rice and rice straw were 0.235 ± 0.014 ppm (n = 48) and 1.149 ± 0.119 ppm (n = 51), respectively. Both were greater than the maximum permissible concentration in drinking water (0.05 ppm; WHO). DOI: http://dx.doi.org/10.3329/bvet.v29i1.11883 Bangl. vet. 2012. Vol. 29, No. 1, 1-6